2008
DOI: 10.1029/2008jc004922
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami forecast analysis for the May 2006 Tonga tsunami

Abstract: [1] This study applies tsunami forecast models developed for NOAA's Tsunami Warning and Forecast System to investigate the May 2006 Tonga Tsunami. Inversion of the Deep-ocean Assessment and Reporting of Tsunamis (DART) measurements estimates a tsunami magnitude equivalent to an earthquake moment magnitude of 8.0. The DARTconstrained modeling forecasts show good agreement with observations at eight coastal tide stations in Hawaii, U.S. West Coast, and Alaska, including first arrival times, wave periods, wave am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 38 publications
2
42
0
Order By: Relevance
“…Tang et al, 2008;Wei et al, 2008;Titov, 2009) shows that the forecast quality obtained by different methods is comparable. The advantage of the proposed method is that it does not require pre-computed database of synthetic tsunami waveforms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang et al, 2008;Wei et al, 2008;Titov, 2009) shows that the forecast quality obtained by different methods is comparable. The advantage of the proposed method is that it does not require pre-computed database of synthetic tsunami waveforms.…”
Section: Resultsmentioning
confidence: 99%
“…This technology was applied in an operative regime for several 2005-2011 major events and demonstrated to be highly efficient (cf. Tang et al, 2008;Wei et al, 2008;Titov, 2009). The maximum wave heights and other parameters of arriving tsunami for several US sites were predicted and were later found to be in good agreement with the actual in situ observed waves (Titov, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution inundation modeling may be required to produce such assessments for coastal locations. TANG et al, (2008) have demonstrated the ability of the flooding forecast models in combination with the tsunami propagation database to reproduce very late arrival of high amplitude trail waves for the May 2006 Tonga tsunami in Hawaii. So the capability of predicting this phenomenon may be at hand, but requires more investigation.…”
Section: Figurementioning
confidence: 99%
“…This event has been considered in detail by several studies, such as Tang et al (2008), Greenslade and Titov (2009) and, in the specific context of T2, Greenslade et al (2010). This event produced no impacts on the Australian coastline or external territories and the desired warning scheme consists of no threats in any coastal zone (not shown).…”
Section: Tonga 2006mentioning
confidence: 99%